Shortcomings and benefits in idle capacity control of Industries in Villavicencio - Fajardo Cortés, Rosa Emilia (Cuadernos de Administración, 2019)
SMEs make up the largest business fabric in Colombia and contribute to the development of the economy, therefore, they have an implicit obligation to be competitive at the national and international level, assuming different challenges, including the implementation of international financial reporting standards, wherefore they require studies that provide performance measurement strategies that allow them to respond to the needs of their environment, as is the case of industries and the effective management of their production costs. Therefore, the objective of this research set out to determine the shortcomings and benefits in the control of idle capacity under the International Financial Reporting Standards— IFRS for SMEs section 13, in the industries of Villavicencio. The methodology used was the case study, and the information was obtained through a structured interview applied to the owners. The results show the shortcomings that arise when financial processes and organizational processes work in a disarticulated manner on the control of idle capacity. They also show the benefits of investing in strategic management tools for cost optimization, leading to the achievement of institutional objectives.